Risk Factors for Pneumonia in Children: A Rapid Survey - Mirasa, Yudied Agung; Sriwahyuni, Efi; Lestari, Evi Noerita; Hendriyanto, Hendriyanto; Eka, Ni Gusti Ayu (Public Health of Indonesia, 2024)
Background: Pneumonia is the leading cause of infection-related death in children globally. East Java, Indonesia, is one of the provinces with the discovery achievement of pediatric pneumonia cases under 70%. Nganjuk Regency, located in East Java, has low discovery achievement of pediatric pneumonia cases (34.64%).  Nganjuk Regency also requires an up-to-date study to determine the current state of pneumonia risk factors. Objective: This study aimed to examine the occurrence of pneumonia in toddlers and its risk factors in Nganjuk Regency East Java, Indonesia. Methods: The design of this study was a cross-sectional using a rapid survey. The participants of this study were 210 housewives or other adult household members having children under five in Nganjuk Regency.  The  study procedure began by collecting data from seven districts wherein each district comprised 30 houses that were chosen purposely. Data analysis was carried out using bivariate and multivariate analysis. The data were analyzed using the statistical software STATA. Results: This study revealed that 18 (7.96%) toddlers had developed pneumonia.  The main risk factors for pneumonia among toddlers in Nganjuk Regency were the nutritional status of toddlers (OR=6.787; 95%CI=1.417-32.525; p=0.017), house cleaning (OR=3.381; 95%CI=1.160-9.851; p=0.026), and room occupancy density (OR=4.191; 95%CI=1.371-12.809; p=0.012). Conclusion: The incidence of toddler pneumonia can be reduced by educating mothers about pneumonia and its risk factors, monitoring toddler growth and nutritional status, and conducting routine surveillance of toddler pneumonia alongside sanitation inspections. Keywords:Children; Pneumonia; Risk Factors; Survey